Business Ethics and Social Ethics in Corporate Social Responsibility (CSR) in the 4.0 Industrial Revolution - Vega Shavira Triswanto (CV ODIS, 2023)
Comparable to individuals, business actors or companies interact with and affect one another through their surroundings and social situations. In addition to chasing profits (profit), a corporation will also focus on giving benefits (benefits) to employees, the community, and the environment. Corporate social responsibility is a program designed to ensure that firms fulfill their responsibilities and are not arbitrary with the human and natural resources in their vicinity (CSR). Corporate Social Responsibility (CSR) has been legally regulated or governed by laws and social principles. In addition to providing material and immaterial advantages to stakeholders, the implementation of CSR will also benefit the organization. Companies devoted to conducting their CSR activities effectively will, of course, have the full backing of their stakeholders.